2010
DOI: 10.1111/j.1365-313x.2010.04352.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis vacuolar anion transporter, AtCLCc, is involved in the regulation of stomatal movements and contributes to salt tolerance

Abstract: SUMMARYIn plant cells, anion channels and transporters are essential for key functions such as nutrition, resistance to biotic or abiotic stresses, and ion homeostasis. In Arabidopsis, members of the chloride channel (CLC) family located in intracellular organelles have been shown to be required for nitrate homeostasis or pH adjustment, and previous results indicated that AtCLCc is involved in nitrate accumulation. We investigated new physiological functions of this CLC member in Arabidopsis. Here we report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
179
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 72 publications
(80 reference statements)
5
179
1
Order By: Relevance
“…For example, the tpk1 mutant of Arabidopsis (Arabidopsis thaliana) removes a major pathway for K + flux across the tonoplast and suppresses stomatal closure, yet the mutant has no significant effect on cellular K + content (Gobert et al, 2007). Similarly, the Arabidopsis clcc mutant eliminates the H + -Cl 2 antiporter at the tonoplast; it affects Cl 2 uptake, reduces vacuolar Cl 2 content, and slows stomatal opening; however, counterintuitively, it also suppresses stomatal closure (Jossier et al, 2010). In work leading to this study, we observed that the slac1 anion channel mutant of Arabidopsis paradoxically profoundly alters the activities of the two predominant K + channels at the guard cell plasma membrane.…”
mentioning
confidence: 55%
“…For example, the tpk1 mutant of Arabidopsis (Arabidopsis thaliana) removes a major pathway for K + flux across the tonoplast and suppresses stomatal closure, yet the mutant has no significant effect on cellular K + content (Gobert et al, 2007). Similarly, the Arabidopsis clcc mutant eliminates the H + -Cl 2 antiporter at the tonoplast; it affects Cl 2 uptake, reduces vacuolar Cl 2 content, and slows stomatal opening; however, counterintuitively, it also suppresses stomatal closure (Jossier et al, 2010). In work leading to this study, we observed that the slac1 anion channel mutant of Arabidopsis paradoxically profoundly alters the activities of the two predominant K + channels at the guard cell plasma membrane.…”
mentioning
confidence: 55%
“…In Arabidopsis thaliana, CLCa and CLCb, both proton-NO 3 -exchangers located in the tonoplast, mediate NO 3 -accumulation in vacuoles (De Angeli et al, 2006;von der Fecht-Bartenbach et al, 2010). Among the other five Arabidopsis CLC proteins, CLCc is involved in chloride transport (Jossier et al, 2010) and CLCd and CLCg possess a selectivity filter in favor of chloride transport (Zifarelli and Pusch, 2009). In Arabidopsis, NRT1 and NRT2 are families of proton-coupled transporters with 53 and seven members, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Essential to stomatal activity, the K + flux within guard cells must be counterbalanced by fluxes of anions, such as Cl − . Thus, it was particularly interesting that a member of the chloride channel family (CLC-c) (Aam081659) that is localized to the vacuole and highly expressed in guard cells in Arabidopsis 41 showed reciprocal expression behaviour in Agave compared with that in Arabidopsis. Collectively, the expression patterns we observed provide substantial evidence for the temporal reprogramming of particular genes essential to regulation of stomatal behaviour in an obligate CAM plant.…”
mentioning
confidence: 99%